Research Trends in Project-Based Learning Models in Facilitating 21st Century Skills: Systematic Literature Review - Sabar Nurohman; Jumadi Jumadi; Suyanta; Sri Rejeki Dwi Astuti; Dhiarrafii Bintang Matahari (Postgraduate, University of Mataram, 2023)
The 21st century is a century where knowledge has increased drastically. Science and technology are growing rapidly and related to human life. Project-based learning is considered as an innovative approach for use in learning in many countries today. So that in the last decade it has raised a lot of interest in researchers to research related to this learning model. Although PjBL is becoming increasingly popular, to date there have been no reviews providing information on the use of PjBL across a wide range of disciplines and at various levels of education. Therefore, this review aims to find out where Project-Based Learning is used, adapted, and researched; and how Project-Based Learning has been used in learning to facilitate 21st century skills over the last 6 years. This systematic literature review used the PRISMA-P 4-step process and bibliometric analysis for 69 appropriate journal articles from 47 journals in 18 countries published from January 2016 to December 2021. A database search was performed with Scopus. The results of this review cover a variety of educational institutions. This review identifies the methods used and their developments over the last 6 years which were published in 69 journal articles in 47 journals in 18 countries and 8 disciplines. The findings are summarized bibliographically and thematically so as to provide important information for educators, researchers and software developers